2012
DOI: 10.1159/000336692
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hemodynamics at 11–13 Weeks’ Gestation in Gestational Diabetes Mellitus

Abstract: Objective: Women who develop gestational diabetes mellitus (GDM) are at increased risk of type 2 diabetes and subsequent cardiovascular mortality and morbidity. Individuals with cardiovascular disorders have increased central aortic systolic blood pressure (SBPAo) and arterial stiffness. The hypothesis of this study is that increased SBPAo and arterial stiffness are apparent before the development of GDM. Methods: In this screening study, SBPAo, pulse wave velocity (PWV) and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
0
16
1
Order By: Relevance
“…The brachial artery waveform readings allow AIx calculation as: AIx (%) = ((P2 − P1)/PP) × 100, where PP is pulse pressure, and thus provides the brachial artery AIx without applying a transfer function. Similar to the Vicorder, there are no validation studies of the Arteriograph in pregnancy; however, it has been used widely in pregnancy research and validated against aortic AIx obtained by cardiac catheterization in a non‐pregnant cohort.…”
Section: Arterial Wave Reflectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The brachial artery waveform readings allow AIx calculation as: AIx (%) = ((P2 − P1)/PP) × 100, where PP is pulse pressure, and thus provides the brachial artery AIx without applying a transfer function. Similar to the Vicorder, there are no validation studies of the Arteriograph in pregnancy; however, it has been used widely in pregnancy research and validated against aortic AIx obtained by cardiac catheterization in a non‐pregnant cohort.…”
Section: Arterial Wave Reflectionmentioning
confidence: 99%
“…Studies of arterial stiffness in complicated pregnancies have focused largely on pre‐eclampsia, intrauterine growth restriction (IUGR), preterm birth and gestational diabetes (GDM), disorders that are associated with a greater risk of a future cardiovascular event in the mother.…”
Section: Arterial Function Studies In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The Arteriograph has been validated against invasive and non‐invasive methods in non‐pregnant populations. Even though there are no direct validation studies of the Arteriograph in pregnancy, it has been used on a very large scale in pregnancy research. Measurements from the Arteriograph had a highly significant correlation with conventional tonometric and piezo‐electric platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported increased arterial stiffness and SBP Ao in women with clinically established PE and GDM16–19. It has been demonstrated recently that SBP Ao and arterial stiffness measured at 11–13 weeks' gestation are increased in women who later develop PE and GDM20–23.…”
Section: Introductionmentioning
confidence: 98%